Exploitation procedure based on eigenvector revisited: the concept of weighted preference flows in multicriteria outranking analysis - Chenayah, S.; Takeda, E. (Kluwer (now part of Springer), 2008)
The outranking analysis has been frequently used to deal with the complex decisions involving qualitative criteria and imprecise data. So far, various versions of ELECTRE have been proposed for ranking alternatives in the outranking analysis. Among others, ELECTRE III has been widely used. A distillation procedure using a qualification index is proposed to rank alternatives from the fuzzy outranking relation. A weakness of ELECTRE III, however, is to involve the arbitrariness in the selection of the discrimination threshold function for the distillation procedure.